OBTENÇÃO DE UM FUNGO COM ALTO PODER HIDROLÃTICO SOBRE BAGAÇO DE CANA PRÉ TRATADO - Vitti, L. S. S.; Silva, D. M.; Vitti, D. M. S. S. (REVISTA DE AGRICULTURA, 2015)
OBTENÇÃO DE UM FUNGO COM ALTO PODER HIDROLÃTICO SOBRE BAGAÇO DE CANA PRÉ TRATADO